Medication use profile in renal transplant patients - Impacts on length of stay (Revista Contexto & Saúde, 2026)
Aim: to evaluate the impact of the medication use profile on the occurrence of complications in kidney transplant patients at a university hospital in Brazil. Methodology: retrospective study using data from renal transplant patients' medical records (n = 182). Interactions between immunosuppressants and other prescribed drugs were analyzed. Results: 68.7% of the patients were male. The average age was 48.15 years. The most frequent comorbidities were hypertension (62.6%) and diabetes (33.5%). The average hospital stay was 21.68 days. 104 drugs were used, 9.71 per patient. As an initial immunosuppressive regimen, 45.1% were prescribed tacrolimus + mycophenolate, 54.4% tacrolimus + sirolimus, and 0.5% mycophenolate + sirolimus. The drugs prescribed with probable interaction with tacrolimus were omeprazole (88.46%), amlodipine (48.90%), and isoniazid (37.91%); with sirolimus, they were amlodipine (29.67%) and isoniazid (20.33%), and with mycophenolate, omeprazole (39.01%). Prescribing a greater number of drugs increased hospitalization time by up to 8.5 days, while the use of calcium channel blockers predicted a reduction of approximately 5 days. Conclusion: The profile of medication use showed that drug prescriptions can have an impact on hospital stay.